IMPLEMENTATION OF DEEP LEARNING APPROACH WITH MEANINGFUL PRINCIPLES BASED ON INDEPENDENT CURRICULUM IN HISTORY LEARNING IN HIGH SCHOOL IN SERANG CITY: Implementasi Deep Learning Approach Dengan Prinsip Meaningful Berbasis Kurikulum Merdeka Dalam Pembelajaran Sejarah Di Sekolah Menengah Atas Kota Serang - Siti Ade Mulyti; Rikza Fauzan, M.Pd; Veri Setiawan, M.Pd (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to determine the implementation of the Deep Learning Approach with Meaningful principles in history learning at senior high schools in Serang City, represented by SMAN 3 Serang City, SMAN 1 Serang City, SMAN 2 Serang City, and SMAN 6 Serang City. This study used a qualitative method with a phenomenological approach, using observation, interviews, and documentation techniques. Based on the findings, the implementation of this approach has varying degrees of success depending on student characteristics and teacher strategies. For example, at SMAN 3 Serang City, SMAN 1 Serang City, and SMAN 2 Serang City, it has been running very well, as seen by the fulfillment of three Meaningful indicators during the classroom learning process. Meanwhile, at SMAN 6 Serang City, it is running well but not yet fully optimal because it is still facing adjustments to student interests and needs. Challenges faced include teachers' limited ability to design and manage learning according to the stages of Deep Learning due to a lack of training. Challenges that arise for students include fatigue, difficulty adapting from passive to active learning patterns, the complexity of history material, and low interest and motivation to learn in some classes.